The first chiral diene-based metal–organic frameworks for highly enantioselective carbon–carbon bond formation reactions. Issue 12 (25th September 2015) - Sawano, Takahiro; Ji, Pengfei; McIsaac, Alexandra R.; Lin, Zekai; Abney, Carter W.; Lin, Wenbin
Abstract : The first chiral rhodium-diene-based metal–organic frameworks are highly active and enantioselective catalysts for C–C bond formation reactions. Abstract : We have designed the first chiral diene-based metal–organic framework (MOF), E2 -MOF, and postsynthetically metalated E2 -MOF with Rh(i ) complexes to afford highly active and enantioselective single-site solid catalysts for C–C bond formation reactions. Treatment of E2 -MOF with [RhCl(C2 H4 )2 ]2 led to a highly enantioselective catalyst for 1, 4-additions of arylboronic acids to α, β-unsaturated ketones, whereas treatment of E2 -MOF with Rh(acac)(C2 H4 )2 afforded a highly efficient catalyst for the asymmetric 1, 2-additions of arylboronic acids to aldimines. Interestingly, E2 -MOF·Rh(acac) showed higher activity and enantioselectivity than the homogeneous control catalyst, likely due to the formation of a true single-site catalyst in the MOF. E2 -MOF·Rh(acac) was also successfully recycled and reused at least seven times without loss of yield and enantioselectivity.